Phytochemical composition and biological activities of Caryopteris grata and Caryopteris odorata from the Nakyal mountains, Azad Jammu, and Kashmir - Shabbir, Mehwash; Ajaib, Muhammad; Mazhar, Muhammad Waqas; Arooj, Zel E; Shabbir, Muneeba (Archives of Biological Sciences, 2025)
Paper description: Leaves of Caryopteris grata and Caryopteris odorata from Azad Jammu and Kashmir (AJK) showed significant variation in phenolic, flavonoid, and tannin contents. GC-MS revealed distinct chemical profiles, with odorata rich in coumarin, phytol, and n-hexadecanoic acid. odorata methanol and ethyl acetate extracts showed stronger antioxidant and cyclooxygenase (COX) inhibitory activities. odorata is a promising natural source for antioxidant and anti-inflammatory agents. Abstract: Medicinal plants Caryopteris grata and Caryopteris odorata from Azad Jammu and Kashmir (AJK), a biodiversity-rich region of the western Himalayas shaped by varied topography and climate, were examined. The Nakyal mountainous zone of the Kotli district represents a distinct ecological niche where plants experience environmental pressures that could influence their phytochemical profiles. Leaf extracts of C. grata and C. odorata were prepared using solvents of varying polarities. We hypothesized that polar extracts would show stronger antioxidant and anti-inflammatory effects. Gas chromatography-mass spectrometry (GC-MS) analysis revealed that C. grata was dominated by 7-methylcyclopenta[c]pyran-4-carboxylic acid methyl ester (61.93%), while C. odorata exhibited a more balanced profile rich in coumarin (30.59%), phytol (10.39%), and n-hexadecanoic acid (7.02%), with both species sharing three compounds but differing markedly in their relative abundance. Dose-response curves revealed that C. odorata exhibited significantly stronger cyclooxygenase (COX) inhibitory activity than C. grata, with methanol and ethyl acetate fractions showing the highest potency. DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging, and ferric thiocyanate (FTC) assays showed clear dose-dependent inhibition by all extracts, with C. odorata, particularly its methanol and ethyl acetate extracts, achieving higher activity at lower concentrations than C. grata. ANOVA with repeated measures for FTC inhibition (24-72 h) exhibited significant effects of species, extract type, and their interaction (P<0.05), with C. odorata methanol and ethyl acetate extracts consistently outperforming other treatments. C. odorata extracts show greater antioxidant and anti-inflammatory potential than C. grata, as indicated by their stronger bioactive profile.